Designing the user interface : recommendations for effective online game interface design focusing on early adult's user / Maziani Malek - Malek, Maziani (2006)
Designing the interface is crucial for online game as it define how the content of the game is flowed. The rapid change of technology had changed the way of interest of designing the interface. The preferences for the design had become more complex as it had to combine the artistic skills, the interface itself and the technology. As designing the good interface should consider the well pleasing, look and feel to the user, it will be appropriate to have a method of consideration for online game. The first problem identified is, there is no primary standard as a reference for designing user interface for online game. That explained the seconds problem where designers wanted to know what is effective and prudence in designing interface based on user and differences in developer point of view. Responding to this problem, this research aimed to come out with recommendations on factor for designing user interface, preferences and avoidance based on user and developer point of view. For deeper understandings, research method such as questionnaires, interviews and observation applied and focused on the early adults between nineteen to twenty four years old. In addition, adults and developer comment gained in order to enhance the interface design. Through this study, data gathered is analyzed and comprised with findings and recommendations. Resulted from all that had been study using software tools- SPSS 11.0 Student Version, an outline of recommendations on effective user interface focusing on target adults were obtained.